Effects of iron supplementation on iron nutrition status and cognitive functions in children - Buzina-Subotičanec, Kornelija; Buzina, Ratko; Stavljenić, Ana Tadinac-Babić, Meri; Juhović-Markus, Vesna (1998)
This study examined the effect of iron supplementation on cognitive function by a double-blind intervention trial in nine-year-old mildly anaemic schoolchildren. Their nutritional status was assessed by anthropometric measurements and the following biochemical values: haemoglobin, haematocrit, red blood cell count (RBC), mean corpuscular haemoglobin (MCH), mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC), serum iron, total iron-binding capacity (TIBC), and transferrin saturation. The cognitive assessment was performed using an abbreviated Wechsler Intelligence Scale for Children-Revised (WISC-R) containing six subtests in order to obtain information on both verbal and non-verbal aspects of intelligence. There were highly significant correlations of the WISC-R scores with initial height-for-age, haemoglobin, haematocrit, and transferrin saturation, and a correlation with MCHC. After completion of the baseline examination, one group of children was given a supplement containing 100 mg of iron for 10 weeks while the other group received a placebo. Iron supplementation had a positive effect on the biochemical measures of iron status and statistically significant improvement in total WISC-R score (p<.01). This effect was primarily the result of improved performance on nonverbal subtests, of which improvements in block design and coding were statistically significant (p<.01). The small increase in the sum of scaled scores from the verbal subtest was not significant (p>.05), but within the verbal subtest there was a significant improvement on the similarities part of the test (p<.05). The effects of iron supplementation were more pronounced in children with initially lower haemoglobin values. It is concluded that iron supplementation in nine-year-old schoolchildren with haemoglobin levels between 110 and 119 g/L will result in an improvement of cognitive functions, even though they are not otherwise malnourished.
ENG